A review on fundamental properties of the jet in the wave environment. (15th April 2022) - Anghan, Chetankumar; Bade, Mukund H.; Banerjee, Jyotirmay
Abstract: Waste water from coastal cities and industries, brine from desalination plants and cooling water from coastal power plants is usually discharged into the receiving water of the ocean from an ocean outfall in the form of a turbulent jet. Discharge of the turbulent jet through an ocean outfall can be modeled as a jet discharged in the wave environment. Effective dilution of the turbulent jet in the wave environment is important in order to minimize pollution of the marine environment. Dilution of the waste water jet in the wave environment can be estimated with the help of various fundamental properties (mean and turbulence quantities) of the jet. In this article, various mean and turbulence quantities of the jet in the regular and random wave environment are first identified from literature. Influence of regular and random waves on the mean properties of the jet such as velocity decay coefficient, jet width and axial velocity profile and turbulence quantities such as axial, lateral turbulence intensity and Reynolds shear stresses are then analyzed in detail based on review of literature. Outcomes of the present study indicate that the ratio of the jet inlet velocity to the wave orbital velocity emerges as a most important parameter in order to understand overall behavior of the jet. The behavior of the jet can be predicted in advance based on the ratio of the jet inlet velocity to the wave orbital velocity. Highlights: Mean and turbulence quantities of the jet in wave environment are outlined. Analysis for horizontal jet in regular waves and vertical jet in regular and random waves. Velocity decay coefficient related to ratio of jet inlet velocity and wave orbital velocity. Self-similarity in axial velocity profiles on the lateral plane observed for weaker waves. A twin peaked axial velocity profile is obtained for a range of wave orbital velocity.